(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the role of T1-weighted dual-echo magnetic resonance imaging (MRI) in the assessment of hepatic steatosis in patients previously diagnosed by ultrasound. Subjects and methods: A retrospective cross-sectional study was conducted on patients diagnosed with hepatic steatosis on ultrasound who subsequently underwent abdominal MRI with dual-echo sequences (In-phase and Opposed-phase) at the National Geriatric Hospital from May 2025 to February 2026. Hepatic fat fraction (HFF) was calculated based on signal intensity differences between in-phase and opposed-phase images. A threshold of HFF ≥ 5% was used to define hepatic steatosis. Results: A total of 17 patients were included, with a mean age of 61.6 ± 10.8 years. Among patients diagnosed with hepatic steatosis on ultrasound, 58.8% met the MRI threshold for hepatic steatosis, while 41.2% did not. The mean HFF of the entire cohort was 8.79%. HFF values were relatively evenly distributed across liver segments, with no statistically significant differences (p > 0.05). Conclusion: Dual-echo MRI may provide additional quantitative information on hepatic fat content in patients diagnosed with hepatic steatosis by ultrasound. However, the observed discrepancy between the two modalities suggests that results should be interpreted with caution. Further studies with larger sample sizes and reference standards are required to establish the diagnostic value of this technique.